2012
DOI: 10.1371/journal.pone.0051271
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Rabbit Parthenogenetic Blastocysts Developed under In Vivo Conditions

Abstract: Parthenogenetic embryos are one attractive alternative as a source of embryonic stem cells, although many aspects related to the biology of parthenogenetic embryos and parthenogenetically derived cell lines still need to be elucidated. The present work was conducted to investigate the gene expression profile of rabbit parthenote embryos cultured under in vivo conditions using microarray analysis. Transcriptomic profiles indicate 2541 differentially expressed genes between parthenotes and normal in vivo fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…The results from the current study are similar to the outcomes of our previous work 220" [30], as development rate to late morula/early blastocyst stage at Day 3 post-activation…”
Section: "supporting
confidence: 91%
See 2 more Smart Citations
“…The results from the current study are similar to the outcomes of our previous work 220" [30], as development rate to late morula/early blastocyst stage at Day 3 post-activation…”
Section: "supporting
confidence: 91%
“…addressed previously [30,31,32]. So, as recommended by these previous studies and by 249" Brevini et al [4] and from the results revealed in this work, the consideration of rates, which although low are those expected for rabbit parthenogenetic embryos.…”
Section: "supporting
confidence: 65%
See 1 more Smart Citation
“…Transcriptomic profile analysis in rabbits indicated that 2541 genes were differentially expressed between parthenotes and normally in vivo fertilized blastocysts. In addition, among those DEGs, 76 genes related to DNA and RNA binding were upregulated and 16 genes related to transport and protein metabolic process are downregulated in in vivo cultured parthenote blastocysts (using a cut-off of 3-fold-change) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…TREX2 was reported to participate in double-stranded DNA break repair [ 59 ]. Alfonso et al found that a DNA repair protein gene was downregulated in rabbit parthenogenetic blastocysts developed under in vivo conditions [ 24 ]. We hypothesized that downregulation of DNA repair proteins may be the major reason why parthenogenesis in rabbits can be induced but cannot develop completely.…”
Section: Discussionmentioning
confidence: 99%